2022
DOI: 10.3389/fphar.2022.927299
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Clinical complete response of advanced renal cell carcinoma associated with Xp11.2 translocation/TFE3 gene fusion by treated by camrelizumab and axitinib: A rare case report

Abstract: Renal cell carcinoma (RCC) associated with Xp11.2 translocation/TFE3 gene fusions is a rare subtype of renal tumor. This entity predominantly occurs in juveniles, but rarely in adults. Xp11.2 translocation RCC (tRCC) patients with lymph node or organ metastasis are associated with poor prognosis, and the strategy remains controversial. Herein, we presented our experience with the diagnosis and treatment of an adult case of Xp11.2 tRCC. In our clinical practice, a 32-year-old male manifested fever and right fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…The patient underwent neoadjuvant therapy with VEGFR-TKI axitinib (5 mg orally once daily) as first-line treatment to reduce the size of the tumor lesion and metastasis. High PD-L1 expression was observed in the PD-L1 immunohistochemistry analysis ( Figure 2F ), which is consistent with previous studies that showed the correlation between PD-L1 expression levels in tumor tissues and the efficacy of PD-1 antibody treatment for TFE3 -rearranged RCC ( 10 , 11 ). Therefore, we administered the anti-programmed cell death-1 antibody tislelizumab (200 mg intravenously once every 3 weeks) targeted therapy.…”
Section: Case Presentationsupporting
confidence: 91%
“…The patient underwent neoadjuvant therapy with VEGFR-TKI axitinib (5 mg orally once daily) as first-line treatment to reduce the size of the tumor lesion and metastasis. High PD-L1 expression was observed in the PD-L1 immunohistochemistry analysis ( Figure 2F ), which is consistent with previous studies that showed the correlation between PD-L1 expression levels in tumor tissues and the efficacy of PD-1 antibody treatment for TFE3 -rearranged RCC ( 10 , 11 ). Therefore, we administered the anti-programmed cell death-1 antibody tislelizumab (200 mg intravenously once every 3 weeks) targeted therapy.…”
Section: Case Presentationsupporting
confidence: 91%